Structure and slow magnetic relaxation in a series of dysprosium(III) complexes - Lv, Hongling; Zhou, Limin; Liang, Huimin; Liang, Yuning; Liu, Dongcheng; Yao, Zaiheng; Hu, Huancheng; Chen, Zilu (Journal of molecular structure, 2025)
•A ligand with pentadentate coordination pocket and two phenolic hydroxyl groups;•Structural diversity from mononuclear, dinuclear, to one-dimensional;•SMM performance tuned through coordination geometry and intermetallic linking modes. With the aim of synthesizing air-stable pentagonal-bipyramidal Dy(III) complexes with a rigid equatorial plane, a pentadentate chelating ligand was used in this work, namely pyridyl-2,6-diacetylbis(salicylhydrazone) (H4L). Its reactions with Dy(OTf)3 gave three Dy(III) complexes, namely [Dyn(H2L)n][Dy(H2L)2]n (1), [Na3(Dy(H2L)2)3(THF)2]n∙5nCH3CN (2) and [Dy2(H2L)2(OMe)2(MeOH)2] (3). The attempted reactions of 3 with Ph3SiOH in the presence of NEt3 gave [Dyn(HL)n] (4). 1 has chain-structured coordination cation of [Dyn(H2L)n]n+ and mononuclear coordination anion of [Dy(H2L)2]−. The Dy(III) coordination unit of [Dy(H2L)2]− in 2 is similar to that of the anion of 1. Interestingly, three [Dy(H2L)2]− units in 2 sandwich two Na+ ions through Na-O bonds to build a linear pentanuclear heterometallic three-decker cluster unit [Na2(Dy(H2L)2)3]−, which is perpendicularly aligned with the neighboring ones through the linkage of Na+ ions, constructing a chain structure. 3 shows a dinuclear structure with the two [Dy(H2L)]+ units double-bridged by two MeO− linkers. 4 exhbits a chain structure similar to that of the coordination cation of [Dyn(H2L)n]n+ in 1. It is revealed from the magnetic measurements that 1, 2 and 4 show slow magnetic relaxation behaviors, and 3 is a field-induced single-molecule magnet. It revealed a tuning effect of SMM performance through coordination geometry and intermetallic linking modes. We report here four Dy(III) complexes prepared from the ligand of pyridyl-2,6-diacetylbis(salicylhydrazone) through tuning reaction solvents and their ratio, with their structures diversified from mononuclear, dinuclear to one-dimensional and their SMM performance tuned through coordination geometry and intermetallic linking modes. [Display omitted]